The role of deterministic succession during forest development within a southern African savanna. (10th March 2021) - Jamison‐Daniels, Samantha‐Leigh; Kissling, W. Daniel; Botha, Monique; Harris, Mathew A.; Gordon, Christopher E.; Greve, Michelle
Abstract: Woody encroachment can lead to a switch from open savannas to dense woodlands or forests. This has implications for both the composition of ecological communities and the provision of ecosystem services such as nutrient cycling and grazing capacity. The patterns and underlying drivers responsible for woody encroachment are not fully understood. Here, we investigate the underlying determinants of bush clump formation (a form of encroachment) in a South African savanna and explore whether bush clump succession is driven by deterministic (i.e., predictable changes in species composition) or stochastic (i.e., random) processes. Specifically, we test (1) whether the similarity in species composition of saplings and trees differs among small and large clumps, (2) which environmental factors are driving succession, and (3) whether forest specialization of tree and sapling species within bush clumps increases with the successional gradient. Similarity in species composition between saplings in small clumps and trees in large clumps was higher than similarity between trees in small clumps and trees in large clumps. Furthermore, temperature, soil moisture, relative humidity, and light intensity were related to changes in species composition along the successional gradient. As expected, forest specialization of trees increased with increasing clump area indicating that late‐successional bush clumps have more forest‐type species. The directional changes of species found along the successional gradient suggest a deterministic process of succession driven by changes in local environmental conditions during clump formation. Abstract : Woody encroachment, in the form of bush clumps, follows a deterministic process of succession. With succession, these clumps alter the microclimate beneath their canopy creating habitat suitable for the establishment of forest‐type species, leading to the establishment of forest islands scattered throughout the savanna.